2021
DOI: 10.1177/03093247211029792
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pore shape on impact dynamics characteristics of functionally graded brittle materials

Abstract: Improving the impact energy dissipation capacity of functionally graded brittle materials through pore design will help avoid or delay failure. In order to improve the impact energy dissipation capacity of functionally graded brittle materials, pores with specific shapes can be implanted inside them. The effect of pore shape on the impact properties of functionally graded brittle materials was investigated using a lattice-spring model that can quantitatively represent the mechanical properties of functionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The higher energy dissipation capability resulted in a better load buffering ability of the scaffold. Normally, the energy dissipation is related to the porosity, while the pore shape is more significant, especially the Poisson’s ratio [ 41 ]. In the present study, the results indicated that the special deformed TPMS unit obtained a stronger energy dissipation capability than square pore, and even the grid scaffold had a higher porosity.…”
Section: Discussionmentioning
confidence: 99%
“…The higher energy dissipation capability resulted in a better load buffering ability of the scaffold. Normally, the energy dissipation is related to the porosity, while the pore shape is more significant, especially the Poisson’s ratio [ 41 ]. In the present study, the results indicated that the special deformed TPMS unit obtained a stronger energy dissipation capability than square pore, and even the grid scaffold had a higher porosity.…”
Section: Discussionmentioning
confidence: 99%